Sağlık Bilimleri Fakültesi öğrencilerinin doku/organ nakli ve bağışı konusunda görüşlerinin belirlenmesi - Sakallı, Gülcan Dürüst (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The aim of this research is to determine the insights of the fourth class students of Health Sciences Faculty at the Eastern Mediterranean University about tissue/organ transplant and donation. The research is designed according to descriptive-sectional research and is held in the Academic Year of 2016-2017 Fall Semester at the Eastern Mediterranean University, Health Sciences Faculty, in the Departments of Nursing, Physiotherapy and Rehabilitation, Nutrition and Dietetic, Health Management and Sports Sciences. The research was applied to 317 fourth class students. Thus, the data was collected from 270 students who volunteered to participate. Data was collected based on the “Student Demographic Information Form” and “Insights of Students on Tissue/organ Transplant and Donation Questionnaire Form”. During the research, ethic board and institution was taken by the students in ainformed conset. Chi-Square of the data with the descriptive analysis and the predictive statistical analysis was used for the statistical analysis of the data. The level of the statistical importance was accepted as ∞=0,05. According to the results of the research, age average of the students was 22.27±2.17, thus 40,7% were male and 59,3% were female. Moreover, 27,8% were from Physiotherapy and Rehabilitation Department, 44,1% were from students of University Entrance Exam, 49,6% were from families whose parents were primary graduates, 38,1% were from families whose parents were from high school graduates and 49,3% were the ones living in states. It was determined that none of the students whom participated in the research have had tissue/organ transplant or donation. 57,4% of these students would like to donate their organs and 88,4% of these students would like to donate their organs for “saving lives”. When the positive feedback of the students for tissue/organ transplant and donation was analyzed, Nursing Department students were the leading students with the ratio of 92,7%. 47,1% of the students have been trained on tissue/organ transplant and donation; thus it was found that statistically training did not have importance on tissue/organ transplant and donation (p<0.05). It was found that the positive feedback of the students on tissue/organ transplant and donation was based on; mother‟s education level, support of the family to organ donation and the department that they studied (p<0.05). It is recommended that in order for the future students of Health Sciences to have positive insights regarding tissue/organ transplant and donation; educational planning, an increase in awareness trainings and tissue/organ transplant and donation campaigns and use of media should be involved. Key Words: Tissue/organ Donation, Tissue/organ Transplant, Students

Öz: Bu araĢtırmanın amacı; Sağlık Bilimleri Fakültesi‟nde öğrenim gören dördüncü sınıf öğrencilerinin doku/organ nakli ve bağıĢı hakkında görüĢlerinin belirlenmesidir. AraĢtırma tanımlayıcı-kesitsel araĢtırma tasarımına uygun olarak yapılmıĢtır. AraĢtırmanın evrenini 2016-2017 akademik yılı güz döneminde Doğu Akdeniz Üniversitesi Sağlık Bilimleri Fakültesi‟nde Beslenme ve Diyetetik, Fizyoterapi ve Rehabilitasyon HemĢirelik, Sağlık Yönetimi ve Spor Bilimleri bölümlerinde öğrenim gören 317 dördüncü sınıf öğrencisi, örneklemini ise araĢtırmaya katılmayı gönüllü olarak kabul eden 270 öğrenci oluĢturmuĢtur. Veriler; “Öğrencilerin Demografik Bilgi Formu” ve “Öğrencilerin Doku/organ Nakli ve BağıĢı Konusunda GörüĢlerinin Belirlenmesine Yönelik Anket Formu” kullanılarak araĢtırmacı tarafından sınıf ortamında toplanmıĢtır. AraĢtırmada etik kurul ve kurum izni, öğrencilerden bilgilendirilmiĢ yazılı onam alınmıĢtır. Verilerin istatistiksel analizinde tanımlayıcı analizler ve kestirimsel istatistik analizlerinden Ki-kare testleri kullanılmıĢtır. Ġstatistiksel önemlilik düzeyi ∞=0,05 olarak kabul edilmiĢtir. AraĢtırmadan elde edilen verilere göre; öğrencilerin yaĢ ortalaması 22.27±2.17 olup, %40,7‟si erkek, %59,3‟ü kadın, %27,8‟i Fizyoterapi ve Rehabilitasyon bölümünden, %44,1‟i Lisans YerleĢtirme Sınavı ile üniversiteye girmiĢ, %49,6‟sının anne eğitim düzeyi ilköğretim ve altı, %38,1‟nin baba eğitim düzeyi lise, öğrencilerin %49,3‟ünün en uzun yaĢadığı yer il‟dir. AraĢtırmaya katılan öğrencilerin doku/organ bağıĢında bulunmadığı saptanmıĢtır. Öğrencilerin %57,4‟ünün organ bağıĢında bulunmak istediği, %88,4‟ünün “hayat kurtarmak için” organ bağıĢında bulunmak istediği belirlenmiĢtir. HemĢirelik bölümü öğrencilerinin %92,7‟sinin organ bağıĢına yönelik olumlu görüĢleri olduğu saptanmıĢtır. Öğrencilerin %47,1‟inin daha önce doku/organ nakli ve bağıĢı hakkında eğitim aldığı ancak eğitim alanların doku/organ nakli ve bağıĢı ile ilgili olumlu görüĢ üzerinde istatistiksel olarak anlamlı etkisinin olmadığı belirlenmiĢtir (p<0.05). Anne eğitim düzeyinin, ailenin organ bağıĢına destek vermesinin ve eğitim aldıkları bölümün, ailenin organ bağıĢına yönelik görüĢlerinin, kendilerine organ naklinin yapılma durumunun, yakınlarının organlarını bağıĢlama durumunun organ nakli ve bağıĢına yönelik olumlu görüĢ bildirmede etkili olduğu saptanmıĢtır (p<0.05). Geleceğin sağlık profesyonellerinin doku/organ nakli ve bağıĢı konusunda olumlu görüĢlerini artırmak için; eğitimlerin planlanması, farkındalık çalıĢmalarının ve doku/organ bağıĢına yönelik kampanyaların artırılması, basın yayın organlarının etkin bir Ģekilde kullanılması önerilir. Anahtar Sözcükler: Doku/organ BağıĢı, Doku/organ Nakli, Öğrenci
Hemşirelik Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Hemşirelik Bölümü, 2017. Tez Danışmanı: Yard. Doç. Dr. Gülten Sucu Dağ.
Keywords: Hemşirelik; Organ Nakli (Organ Bağışı); Doku/organ bağışı; doku/organ nakli; öğrenci; Tissue/organ donation; tissue/organ transplant; students